Hubungan Jumlah Eritrosit dan Hitung Jenis Leukosit pada Masyarakat dengan Paparan Polutan Tinggi di Desa Tambak Mulyo Kota Semarang - Eko Naning Sofyanita; Hendra Adistia Bangkit; Roni Afriansya (Borneo Journal of Medical Laboratory Technology, 2021)
Lead (Pb) and carbon monoxide (CO) are gas components in airborne pollutants due to vehicle fumes or industrial exhaust gases that affect the blood, namely shortening the life span of erythrocytes produced in erythropoiesis. In addition, small pollutants can be inhaled and enter the alveoli and then phagocytosis and trigger the release of mediators, namely leukocyte cells, which can cause inflammation. This study aims to determine the correlation between the erythrocytes count and differential leucocyte count of the Tambak Mulyo village community, Semarang City. This research was a cross-sectional analytic study of primary data using 20 blood samples, carried out by the erythrocytes count and differential leucocyte count tests. The examination results showed that the average erythrocytes count in all samples was 5.25 million cells/mm3 with a percentage of the normal erythrocytes count is 45.00%, and a high of erythrocytes count is 55.0%. On the test of the differential leucocyte count, 4 samples are obtained with specific values. Normal leukocytes and as many as 16 samples experienced an increase and decrease in the differential leucocyte count. The chi-square test shows Asymp.Sig> 0.05, which means there is no correlation between variables, so it can be concluded that there is no significant correlation between the erythrocytes count and differential leucocyte count (lymphocytes, basophils, eosinophils, neutrophils, and monocytes) in the community with exposure to high pollutants in Tambak Mulyo village, Semarang City.